2009
DOI: 10.1155/2009/821543
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Survivin and Cortactin in Colorectal Adenocarcinoma: Association with Clinicopathological Parameters

Abstract: Objective: Survivin and cortactin are factors that promote tumor progression. We tested the hypothesis that survivin and cortactin expressions correlate with the clinico-pathological parameters of colorectal adenocarcinomas and survival time. Methods: Immunohistochemical analysis of survivin and cortactin were performed using tissue microarrays of 119 specimens from 18 well, 50 moderately, and 27 poorly differentiated colorectal adenocarcinomas and 24 colorectal adenomas with dysplasia. As control, 10 specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 34 publications
1
34
0
2
Order By: Relevance
“…Cortactin overexpression is known to be associated with the development of cancer (7)(8)(9)(10)(11). The overexpression of cortactin obtained by immunohistochemistry in 62.5% cases of colorectal cancer is consistent with previous findings.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Cortactin overexpression is known to be associated with the development of cancer (7)(8)(9)(10)(11). The overexpression of cortactin obtained by immunohistochemistry in 62.5% cases of colorectal cancer is consistent with previous findings.…”
Section: Discussionsupporting
confidence: 90%
“…The C-terminal half is composed of an ·-helix domain of unknown function, followed by a proline-serine-threonine-rich region (PST) and Src homology 3 (SH3) domain (6). Gene amplification of CTTN and overexpression of cortactin have been reported in various cancers including colorectal cancer (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Lee et al [50] found that higher expression of survivin correlates significantly with tumor stage and shorter survival time. Our study showed that survivin is expressed in the majority of colorectal carcinomas and is associated with tumor grade.…”
Section: Discussionmentioning
confidence: 99%
“…(27) noted that the immunohistochemical reaction of survivin was associated with the presence of metastases and disease relapse in CRC patients. Moreover, Lee et al (28) showed that the positive expression of survivin was closely associated with primary tumor and distant metastasis categories, and with tumor stage. The present detailed analysis revealed a positive correlation between survivin located in the nucleus of cancer cells in CRC patients and distant metastases and tumor location.…”
Section: Survivin (Pg/ml) -------------------------------------------mentioning
confidence: 99%